Catalog of Offshore Seismicity in Cascadia: Insights Into the Regional Distribution of Microseismicity and its Relation to Subduction Processes. Issue 1 (29th January 2018) - Stone, Ian; Vidale, John E.; Han, Shuoshuo; Roland, Emily
Abstract: We present a catalog of offshore seismicity generated from Cascadia Initiative (CI) ocean‐bottom seismometer data. Earthquakes were detected within the CI data using a short‐time‐average/long‐time‐average trigger and located using 1‐D velocity models developed from seismic reflection/refraction surveys. The catalog, which contains 271 earthquakes with magnitude 0.4–4.0 along the coasts of Vancouver Island, Washington, Oregon, and Northern California, spans all 4 years of the ocean bottom seismometer deployment and shows distinct along‐strike variations in seismicity consistent with structural observations from recent active source seismic reflection/refraction studies. Seismicity is sparse off Vancouver Island and Washington (49°N–46°N) but increases off northern and central Oregon, corresponding to a roughened, more deformed subducting slab. Widespread earthquakes are observed at near‐interface depths between 46°N and 45°N, though an increase in underthrust sediment thickness between 45°N and 43°N likely restricts seismicity to scattered asperities on the plate interface. South of 43°N, where both the overriding and subducting plates are severely deformed approaching the Mendocino triple junction, seismicity is abundant. We locate an additional 440 events in the Juan de Fuca plate seaward of the deformation front. The higher seismicity south of 46°N is consistent with more extensive intraplate deformation. Along with the complex stress field induced by the Mendocino triple junction, our observations imply that the smoothness and degree of hydration of the incoming plate, which are linked to the amount of underthrust sediment and extent of intraplate deformation, are major contributing factors to the distribution of microseismicity in the Cascadia subduction zone. Key Points: We develop an earthquake catalog using the Cascadia Initiative ocean bottom seismometer data set for the entire Cascadia subduction zone Subduction zone and Juan de Fuca plate seismicity increases from north to south, with distinct increase in seismicity south of 46°N Seismicity varies with incoming plate smoothness and hydration, tied to observed trends in intraplate deformation and underthrust sediment